Low power and reliable SRAM memory cell and array design - Ishibashi, Koichiro; Osada,Kenichi (Springer, 2011)
Success in the development of recent advanced semiconductor device technologies is due to the success of SRAM memory cells. This book addresses various issues for designing SRAM memory cells for advanced CMOS technology. To study LSI design, SRAM cell design is the best materials subject because issues about variability, leakage and reliability have to be taken into account for the design.